Clinical, epidemiological, and mycological features of patients with candidemia: Experience in two tertiary referral centers in Iran - Mohammad Kord; Mohammadreza Salehi; Seyed Jamal Hashemi; Alireza Abdollahi; Neda Alijani; Ayda Maleki; Shahram Mahmoudi; Kazem Ahmadikia; Nasrin Parsameher; Masoud Moradi; Mahsa Abdorahimi; Sara Rezaie; et al. (Mazandaran University of Medical Sciences, 2022)
Background and purpose: Candidemia is a major cause of morbidity and mortality among patients receiving immunosuppressive therapy and those hospitalized with serious underlying diseases. Here, we investigated the epidemiological, clinical and mycological features of candiemia in Tehran, Iran.Material and methods: A prospective observational study of all patients diagnosed with candidemia was performed at two referral teaching hospitals in Tehran, Iran between February to December 2018. Demographic characteristics, underlying diseases, risk factors, clinical symptoms, and laboratory analyses of candidemic patients with positive culture were mined. Candida isolates were molecularly identified by sequencing of the internal transcribed spacer region (ITS1-5.8S-ITS2). The antifungal susceptibility testing for fluconazole, itraconazole, voriconazole, posaconazole, amphotericin B, caspofungin, micafungin and anidulafungin against the isolates were performed using CLSI broth microdilution reference method (M27-A3).Results: A total of 89 episodes were identified, with an incidence of 2.1 episodes/1000 admissions. The most common underlying disease was sepsis (48%) followed by malignancy (46%), renal failure/dialysis (44%), and hypertension (40%). The overall crude mortality was 47%. C. albicans (44%) was the most frequent causative agent followed by C. glabrata (21%), C. parapsilosis complex (15%), C. tropicalis (11%), and C. lusitaniae (3.5%). All the isolates were susceptible to amphotericin B. The activity of all the four azoles was low against non-albicans Candida species, especially C. tropicalis.Conclusion: Increase in non-albicans Candida species with reduced susceptibility to antifungal drugs might be alarming in high-risk patients. Therefore, accurate knowledge of predisposing factors and epidemiological patterns in candidemia are effective steps for managing and decreasing the mortality rate in candidemia.